Patient satisfaction with pharmacy services in Kediri city pharmacies - Maharani Dwi Pratiwi; Abdul Rahem; Wahyu Utami (Jurnal EduHealth, 2024)
Patient satisfaction is considered an essential indicator of the outcomes of pharmaceutical services. This study aimed to assess patient satisfaction with the pharmaceutical services in Kediri, and to knowing what services that make patient feels satisfying. A cross sectional study was conducted by administering the questionnaire using accidentally sampling in 27 Pharmacy in Kediri. A questionnaire instrument using SERVQUAL method. Respondens were selected by accidental sampling. Gap results being the difference between what patient expects and what patient receives. Descriptive statistics were calculated for satisfaction scores in Tki Score and cartesian diagram by comparing perception and expectation. Data of 108 patients were analyzed. A negative score in Gap analyze. The overall Tki score was 82,64%. The services that must be maintained are services in the assurance dimension and the empathy dimension. In the services that are a low priority for improvement are the tangible dimension and the reliability dimension. There are no services that are a top priority for improvement because the patient is already satisfied. Overall, patients are satisfied with the services. Our study showed that patients in Kediri were the services is under expectation. The services that must be maintained are services in the assurance dimension and the empathy dimension. Patients in Kediri were feels satisfied with the pharmaceutical services provided